Isolation, identification, and sensitivity profile of Bacillus spp. in co-infection with respiratory viruses - Chagas, Angelica de Lima das; Araújo, Joilma Cruz da Silva; Vieira, Jose Daniel Goncalves; Avelino, Melissa Amelotti Gomes; Carneiro, Lilian Carla (Frontiers in Pediatrics, 2026)
This study investigates the occurrence and antimicrobial susceptibility of Bacillus spp. in pediatric patients with viral respiratory infections admitted to intensive care units. Secondary bacterial infections are known to exacerbate the severity of viral respiratory diseases and represent a major cause of morbidity and mortality during pandemics, including COVID-19. A total of 659 respiratory samples from children with respiratory symptoms hospitalized in five hospitals were analyzed. Bacterial co-infections were identified by inoculation in BHI medium and confirmed by MALDI-TOF. Antimicrobial susceptibility testing was performed using the Kirby-Bauer method, following EUCAST guidelines. Among 166 cases of bacterial co-infection, 20 (12.05%) were attributed to Bacillus spp., with a predominance in patients infected with respiratory syncytial virus (55%). The isolates showed high susceptibility to vancomycin (85%), imipenem (80%), erythromycin (70%), and ciprofloxacin (65%). These findings reveal that Bacillus spp., often considered an environmental contaminant, may play a clinically relevant role in pediatric viral co-infections, particularly in severe respiratory cases. This study contributes novel data to a poorly explored area of pediatric infectious disease research, emphasizing the need for routine susceptibility testing to optimize antimicrobial therapy. The results provide a foundation for future molecular studies on Bacillus spp. virulence and resistance mechanisms, supporting evidence-based management and infection control practices in critical care settings.